2018
DOI: 10.1177/8756972818788773
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Innovation in Oil and Gas Projects

Abstract: We examine the effects of predictors from the firm, project, and individual levels on innovative behavior within oil and gas projects. The theory and propositions tested in this study stem from extant work on (1) innovation in poor performance conditions and (2) the availability of slack resources. The research findings revealed that innovative behaviors were present regardless of size, type, and project performance level. Further, it appears that the relationship between slack and innovation depends on when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 149 publications
(186 reference statements)
0
4
0
Order By: Relevance
“…The types and frequency of problems that need solving will depend on the types of projects, their complexity, duration, and pace (Biedenbach & Müller, 2012;Nachbagauer & Schirl-Boeck, 2019). For instance, the oil and gas industry's technical challenges may require a particular problem-solving frequency that may not be as evident in other settings (Olaniran et al, 2015;Rahimi et al, 2018;Stinchcombe & Heimer, 1985). Interfirm projects from other sectors should therefore be targeted for replication.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…The types and frequency of problems that need solving will depend on the types of projects, their complexity, duration, and pace (Biedenbach & Müller, 2012;Nachbagauer & Schirl-Boeck, 2019). For instance, the oil and gas industry's technical challenges may require a particular problem-solving frequency that may not be as evident in other settings (Olaniran et al, 2015;Rahimi et al, 2018;Stinchcombe & Heimer, 1985). Interfirm projects from other sectors should therefore be targeted for replication.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…The operationalization of the business ecosystem strategy and associated action patterns dealt with in this article, being one of the objectives, opens up new avenues for deductive research in the context of complex capital projects. Such research will address the call for theory-driven research for projects (Rahimi, Kenworthy, & Balakrishnan, 2018) of the ecosystem in the wider context (Söderlund et al, 2017) at the macro-level (Geraldi & Söderlund, 2018). Noble Laureate for Physics, Robert Laughlin, observed that "science has moved from an Age of Reductionism to an Age of Emergence, a time when the search for ultimate causes of things shifts from the behavior of parts to the behavior of the collective" (2005, p. 208;cited in Comello, 2012).…”
Section: Conclusion and Future Research Agendamentioning
confidence: 99%
“…PMs have become increasingly important figures (Papke-Shields et al, 2010), responsible for initiatives that typically feature substantial uncertainty, ambiguity and complexity (Lenfle, 2008); innovation (Rahimi et al, 2018); and change (Voropajev, 1998). Further, PM actions often impact overall business performance.…”
Section: Introductionmentioning
confidence: 99%